Mass mediated representations of crime and criminality - Wiest, Julie B. (Studies in media and communications ;, 2021)
Sponsored by the Communication, Information Technologies, and Media Sociology section of the American Sociological Association (CITAMS), this volume of Studies in Media and Communications features social science research that examines the practices, patterns, and messages related to representations of crime in mass media around the world. Chapters focus on a wide range of fact-based and fictional accounts of criminality as depicted in print and broadcast news, documentary and video-on-demand films, and television programs. Stories about crime and criminality have long been the mainstay of news and entertainment media content, and the intersection of crime and media is a common topic in scholarly research. Moreover, substantial evidence indicates that these media depictions are highly influential as people in economically advanced societies- who tend to have little personal experience with crime-form perceptions about criminality, crime rates, characteristics of criminals, and even their own likelihood of victimization. Thus, ongoing examination of crime images within various types of mass media aids in understanding the associated messages and meanings that are disseminated to consumers. This volume will enhance the knowledge of junior and senior scholars in criminology, sociology, journalism, and communication/media studies, particularly because of its inclusion of crime stories in a variety of formats and that represent media content from nations spanning five continents.